Policy Analysis For the Determination of BIPIH For Indonesian Hajj Pilgrims in 2023 - Hendrizal; Syamsir; Aldri Frinaldi (Ilomata International Journal of Social Science, 2023)
The policy of determining Bipih (Hajj Travel Expenses) is a policy made by the Indonesian government to determine the costs to be paid by Indonesian Hajj pilgrims in carrying out Hajj in Mecca. This type of research was carried out using qualitative descriptive methods and analyzed using the SWOT method by utilizing secondary data in the form of Bipih increase policies in 2023 issued by the Ministry of Religious Affairs of the Republic of Indonesia. The source of the data can be found on the official website of the Ministry of Religious Affairs of the Republic of Indonesia, namely Kemenag.go.id and haji.kemenag.go.id. The government this year increased costs due to the imbalance in the value of benefits that have been going on starting from 2018 so that the policy of increasing Bipih in 2023 became the government's choice. Because the announcement period is very close to the announcement of the repayment of Bipih pilgrims, and this creates cons in the community. The increase in Bipih aims for the sustainability of the value of benefits for pilgrims who will depart in the coming years. Furthermore, it is advisable to do policy planning better and the Government through public relations must also provide information gradually and continuously to the public regarding the increase in Bipih.